The strategy of three education centers for strengthening character education in Indonesia in the era of Industrial Revolution 4.0 - Marzuki, Marzuki; Samsuri, Samsuri (Universitas Negeri Yogyakarta, 2022)
Education plays an important role in developing the character of a nation. Education is not only implemented in formal education institutions, but also in the family and amongst the community. This study aims to describe the three-center education strategy in Indonesia for strengthening character education in the era of industrial revolution 4.0, and to obtain an overview of the feasibility of infrastructure in schools that support the implementation of strengthening character education appropriately through this strategy. This research is a qualitative descriptive study conducted in three junior high schools (SMP) that were piloted for the strengthening of character education in Yogyakarta, Indonesia. The research subjects included the students, teachers, education personnel, parents of students, and community leaders. Data collection used interviews, observations, documentation, and a focus group discussion (FGD). Data analysis was performed with the interactive technique of the Miles and Huberman model. The results showed that the strengthening of character education in schools in the era of industrial revolution 4.0 is carried out well through the strategy of three education centers. Three state junior high schools in Bantul, Yogyakarta, namely SMPN 1 Bantul, SMPN 1 Sewon, and SMPN 1 Pandak, have implemented character strengthening for students using the strategy of three education centers appropriately. In general, the support for the facilities and infrastructure for the strengthening character education programs is sufficient, allowing the character education strengthening program to run well.